2018
DOI: 10.1051/0004-6361/201732367
|View full text |Cite
|
Sign up to set email alerts
|

New measurements of D/H on Mars using EXES aboard SOFIA

Abstract: The global D/H ratio on Mars is an important measurement for understanding the past history of water on Mars; locally, through condensation and sublimation processes, it is a possible tracer of the sources and sinks of water vapor on Mars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…On this planet, the D/H budget is dominated by H 2 O and HDO which are the unique precursors of the escaping D and H atoms above the exobase. HDO was previously measured as column-integrated abundances from Earth [31][32][33] and in situ 34 by the Mars Science Laboratory. NOMAD and ACS provide for the first time the capability to observe the vertical distribution of HDO simultaneously with water vapour, thereby providing key information on the fractionation processes that are expected to control the amount of hydrogen and deuterium atoms escaping to space 25 .…”
Section: The Fractionation Between H 2 O and Hdo Is An Important Procmentioning
confidence: 99%
“…On this planet, the D/H budget is dominated by H 2 O and HDO which are the unique precursors of the escaping D and H atoms above the exobase. HDO was previously measured as column-integrated abundances from Earth [31][32][33] and in situ 34 by the Mars Science Laboratory. NOMAD and ACS provide for the first time the capability to observe the vertical distribution of HDO simultaneously with water vapour, thereby providing key information on the fractionation processes that are expected to control the amount of hydrogen and deuterium atoms escaping to space 25 .…”
Section: The Fractionation Between H 2 O and Hdo Is An Important Procmentioning
confidence: 99%
“…Similar trends have been found for properties of upper atmospheric hydrogen at Mars (Bhattacharyya et al, ; Clarke et al, , ; Halekas, ). Studies of water variability lower in the atmosphere, using spectral analysis of H 2 O and HDO as well as using simulations, have shown seasonal differences in the distribution of water and its isotopologues lower in the Martian atmosphere (Encrenaz et al, ; Encrenaz et al, ; Fedorova et al, ; Krasnopolsky, ; Montmessin et al, ; Villanueva et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This led M05 to predict a latitudinal gradient of D/H (with variations greater than a factor of 5) between the warm and moist summer hemisphere and the cold and dry winter hemisphere. This gradient was later confirmed by several Earth ground-based and Mars orbiting assets (Aoki et al, 2019;Encrenaz et al, 2018;Krasnopolsky, 2015;Villanueva et al, 2015). Yet some observations (Khayat et al, 2019;Villanueva et al, 2015) have revealed longitudinal variations of D/H ratios in appearance correlated to topography that were not reproduced by any model.…”
mentioning
confidence: 87%